2002
DOI: 10.1039/b208458a
|View full text |Cite
|
Sign up to set email alerts
|

Shape fabrication of millimeter-sized metal-containing carboxymethyl cellulose hollow capsules

Abstract: Dropwise addition of an aqueous carboxymethyl cellulose solution to a solution of a copper or iron salt in n-butanol, leads to self-assembled, permeable millimeter sized metal-ion derivatized carboxymethyl cellulose hollow capsules of uniform dimensions and different morphologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Nagai et al developed poly­(dimethylsiloxane)-encapsulated poly­(amic acid) capsules with a diameter of 0.5–5 mm by injecting poly­(dimethylsiloxane) into poly­(amic acid) spheres and curing the resulting capsules at high temperature. Bourlinos and Petridis developed millimeter-sized polymeric capsules by dropwise adding an aqueous carboxymethyl cellulose solution into an n -butanol solution with copper or iron salt. Recently, millimeter-sized capsules were prepared using liquid marbles by dropwise adding a trimethylolpropane trimethacrylate monomer droplet on superamphiphobic powders, rolling it to form liquid marbles, injecting water droplet into the liquid marbles, and irradiating them by visible light .…”
Section: Introductionmentioning
confidence: 99%
“…Nagai et al developed poly­(dimethylsiloxane)-encapsulated poly­(amic acid) capsules with a diameter of 0.5–5 mm by injecting poly­(dimethylsiloxane) into poly­(amic acid) spheres and curing the resulting capsules at high temperature. Bourlinos and Petridis developed millimeter-sized polymeric capsules by dropwise adding an aqueous carboxymethyl cellulose solution into an n -butanol solution with copper or iron salt. Recently, millimeter-sized capsules were prepared using liquid marbles by dropwise adding a trimethylolpropane trimethacrylate monomer droplet on superamphiphobic powders, rolling it to form liquid marbles, injecting water droplet into the liquid marbles, and irradiating them by visible light .…”
Section: Introductionmentioning
confidence: 99%
“…Sodium carboxymethyl cellulose (CMC) (Scheme ), a nontoxic and biodegradable cellulose derivative, has been used widely in biotechnology, , medicine, , hydrogels, and other materials. Recently, CMC has been used as a good stabilizer in the synthesis of metal nanoparticles in an aqueous medium. However, reducing agents such as NaBH 4 were still used in these studies. More recently, cellulose was used as the reducing regent in Au(III)−Au(0) reduction and also as a moderately efficient template for the formation of various micrometer-sized gold particles .…”
Section: Introductionmentioning
confidence: 99%
“…Petridis et al reported that dropwise addition of CMC solution to a Cu or Fe salt in n-butanol leads to self-assembled, permeable, millimeter-sized metal-ion-derivatized CMC hollow capsules. 30 Herein, we report a simple and convenient approach that generates nanocomposites at room temperature in aqueous medium, encompassing various metal salts such as Cu, In, Fe, and Ag, and these materials may find potential applications such as in antibacterial, antifungal coatings, food packaging, and biomedical devices.…”
Section: Introductionmentioning
confidence: 99%